Development of Education, Health and Social Service as an Implementation of Al-Maun Theology to Strengthen the Welfare of Community Life in Pucung Village, Wonogiri - Ibnu Rushd, Dartim; Muhammad Wildan Shohib; Mohamad Ali; Mohamad Nur Rochim Maksum; Nurul Latifatul Inayati (Abdi Psikonomi, 2025)
This community service program (PkM) aims to address significant welfare gaps in remote areas. Such as in rural areas in Wonogiri Regency, Central Java. This PkM focuses on integrated Islamic religious education, health and social services as an actualization of Al-Maun theology initiated by KH Ahmad Dahlan (founder of Muhammadiyah). Islamic religious education services, especially in remote areas such as Pucung Village, Eromoko District, Wonogiri are among the most concerning. Due to various limitations, such as lack of teachers, minimal educational facilities, minimal social activities and a quality of life that is far from healthy. This fact encourages the PkM Team to provide solutions in the form of programs and activities designed to improve the quality of life of the community in terms of education, health and social. Guidance activities are carried out with religious guidance to improve understanding and quality of worship and other Islamic education. Muhammadiyah Post School which provides non-formal education at the ronda post. In addition, there is also Health Education to increase health awareness in the community. This program will involve various stakeholders, including local governments, schools, communities, and religious organizations. Through good collaboration, it is hoped that it can create a conducive, sustainable living environment that can reflect the characteristics of Al-Maun theology with a focus on the three areas as mentioned.